Qualidade higiênico-sanitária e quimica do leite e avaliação de impactos ambientais e sociais, após a utilização do kit embrapa de ordenha manual® para caprinos leiteiros - Andrade, Patrícia Lopes (2012)
The northeastern region of Brazil has great potential for the production of goat milk, and the quality of the milk produced is important to ensure consumers a safe food supply from the nutritional and hygienic-sanitary standpoint. Goat milk has high nutritional value and has a wide acceptance, especially in poor communities, since it is an important protein source in the diet of these people. The free and daily distribution of the goat milk, through government programs, aims to reduce nutritional deficiencies with priority given to children, pregnant women and nursing mothers. The goal of this study was to evaluate the effect of the Kit Embrapa de Ordenha Manual® for dairy goats in family farming, located in three regions of northeastern Brazil. This effect was evaluated in samples of goat milk on the composition, somatic cell count (SCC) and total bacterial count (TBC), and also the effect of SCC on the components, by correlation of the data. In parallel, we assessed the environmental and social impacts of the Kit through Sistema Ambitec-Agro. The Kit Embrapa de Ordenha Manual® was developed with the purpose of safe milk production through a low-cost technology that is available to family farmers, who are responsible for much of the production of goat milk in Brazil. Its validation in properties of Paraiba, Rio Grande do Norte and Ceará brought positive results, as the average of TBC decreased 72% and the characteristics of milk composition were preserved. The evaluation of SCC effect on the milk components showed that there was a decrease in the percentage of lactose in milk as SCC increased. Among the samples analyzed, 64% had counts exceeding 1.000.000 CCS/mL. This highlights the need for the implementation of hygiene practices on the milking properties evaluated. The social and environmental impact was also positive, with average values of 1.07 and 0.9 in the ex post evaluation indexes for Environmental and Social Impact, respectively, showing the potential of this technology as part of a set of attitudes capable of improving the quality of goat milk produced in Brazil, as well as of providing gains to producers.